DEFINITION OF ‘FOREIGN PUBLIC OFFICIAL’ IN THE OECD CONVENTION ON COMBATING BRIBERY OF FOREIGN PUBLIC OFFICIALS IN INTERNATIONAL BUSINESS TRANSACTIONS - Limantė, Agnė; Limantas, Manfredas (Teisė, 2017)
The article analyses 1997 OECD Convention on Combating Bribery of Foreign Public Officials in International Business Transactions, which became of particular importance to Lithuania due to its recent accession to this international agreement. The article focuses on the content of the concept of ‘foreign official’.